2010
DOI: 10.1007/s12032-010-9610-4
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic factors for Krukenberg tumor: a clinical study on 102 cases

Abstract: To investigate factors associated with gastrointestinal (GI) carcinomas metastasizing to ovaries to form Krukenberg tumor. Among the 102 cases of Krukenberg tumor due to GI cancers, there were 41 cases synchronously diagnosed, 43 cases with primary tumor identified first and 18 cases with ovarian tumor identified first. Metastatic factors of 43 cases of metachronous Krukenberg tumor were analyzed with univariate and multivariate methods. Of the 43 patients, the median age at diagnosis of Krukenberg tumor was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…So attention should always be paid regarding transcoelomic metastasis to ovaries from advanced GI carcinomas. The study result of Li Qiu et al showed the 1-year and 2-year metastasis-free survival rates were 48.5% and 18.2% in T3 group, compared with 14.3% and 0 in T4 group (P = 0.031) [10].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…So attention should always be paid regarding transcoelomic metastasis to ovaries from advanced GI carcinomas. The study result of Li Qiu et al showed the 1-year and 2-year metastasis-free survival rates were 48.5% and 18.2% in T3 group, compared with 14.3% and 0 in T4 group (P = 0.031) [10].…”
Section: Discussionmentioning
confidence: 96%
“…There is a major chance of cancer cells invading the ovaries when the serosal layer or tissue beyond is invaded by GI cancer in female patients. Based on the cases of advanced T stage of primary GI cancer, the tumor cells could easily be scattered into the peritoneal cavity forming a metastasis to ovaries [7] [10]. So attention should always be paid regarding transcoelomic metastasis to ovaries from advanced GI carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphatic and hematogenous spread, especially lymphatic spread is widely believed to play the possible role in cancer metastasis from the primary gastrointestinal site to the ovaries. But here, we would like to discuss the role of transcoelomic spread and rupture in the ovary (wound) during ovulation providing favorable seeding site as a major route of metastasis [9].…”
mentioning
confidence: 99%